Impact of Community Education on Antenatal Care Visits in Bangladesh: A Multilevel Analysis - Rahman, Md Morshadur; Hossain, Md Akhtar (Dhaka University Journal of Science, 2019)
Antenatal care (ANC) utilization has a great role in reducing pregnancy-related complications and maternal mortality. Besides individual demographic and socio-economic factors, community characteristics can influence a mother‟s decision to seek antenatal care visits. This study makes an attempt to determine the influence of community education on adequate ANC visits in Bangladesh by using Bangladesh Demographic and Health Survey (BDHS) 2014 data. Multilevel logistic regression model has been employed for the purpose of the analysis. Study findings showed a significant positive association of community education on adequate ANC visits. Other community and individual level covariates such as place of residence, region of residence, birth order, mother‟s age at birth, household wealth, media access, husband‟s education, decision making on health care also showed significant association with adequate ANC visits. Dhaka Univ. J. Sci. 67(1): 41-46, 2019 (January)